2021
DOI: 10.1039/d0cs00948b
|View full text |Cite
|
Sign up to set email alerts
|

Advances in applied supramolecular technologies

Abstract: Supramolecular chemistry has successfully built a foundation of fundamental understanding. However, with this now achieved, we show how this area of chemistry is moving out of the laboratory towards successful commercialisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 204 publications
(276 reference statements)
0
76
0
Order By: Relevance
“…As an example, dexamethasone carried by soluble nanoparticle (drug name OCS-01) developed by Oculis is now in a phase III clinical trial for DME. The results of a phase II (DX-211) study demonstrated that OCS-01 as a topical eye drop formulation could significantly reduce central macular thickness and improve the visual acuity compared with the vehicle arm [ 13 , 14 ].…”
Section: Innovations That Increase Intraocular Bioavailability Of Topical Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, dexamethasone carried by soluble nanoparticle (drug name OCS-01) developed by Oculis is now in a phase III clinical trial for DME. The results of a phase II (DX-211) study demonstrated that OCS-01 as a topical eye drop formulation could significantly reduce central macular thickness and improve the visual acuity compared with the vehicle arm [ 13 , 14 ].…”
Section: Innovations That Increase Intraocular Bioavailability Of Topical Drugsmentioning
confidence: 99%
“…There have been extensive explorations to enhance the delivery efficiency of topical formulations [7][8][9]. Currently, only a few topical formulations to target the posterior segment are in clinical development, including a dexamethasone in cyclodextrin microparticle formulation for the treatment of diabetic macular edema (DME) (phase II/III) [10], difluprednate emulsion for the treatment of DME (off-label use) [11], Aganirsen emulsion for the treatment of ischemic central retinal vein occlusion (phase II/III) [12], and OCS-01 in a soluble nanoparticle formulation for the treatment of DME (phase III) [13,14]. However, in recent years, the emerging science of new materials has brought possibilities for generating many novel topical drug formulations, which receive increasing attention in preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond nature, the research into supramolecular assembly has rapidly progressed in recent years, enabling the design of materials with precisely tuned properties and functionalities [5,6]. The applications of supramolecular structures are as multifaceted as the underlying molecules.…”
Section: Introductionmentioning
confidence: 99%
“…There has been significant progress in the design of molecular anion receptors characterized by high selectivity and efficiency in recent years. The use of anion binding domains tethered to appropriate molecular platforms has allowed a number of molecular receptors to be obtained, with applications in medicine, environmental remediation, and many industrial processes [ 1 , 2 , 3 , 4 ]. In particular, modifying anion receptors with a signaling unit has led to selective sensors [ 5 , 6 , 7 , 8 , 9 ]; incorporating strong and/or multiple binding domains into the receptor scaffold results in effective extractants that are able to operate in both solid–liquid and liquid–liquid conditions [ 10 ]; carefully balancing the strength of the receptor binding domains gives rise to transmembrane transporters [ 11 , 12 , 13 , 14 ]; and harnessing the interaction of the binding site with particular anions opens up the possibility of them acting as organocatalysts [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%